USING SHADOWING TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN LISTENING COMPREHENSION - Febrika Dwi Lestari (JETAL: Journal of English Teaching & Applied Linguistic, 2020)
This study was aimed to observe the use of Shadowing technique to improve students’ ability in listening comprehension. This research was conducted by using classroom action research which is consist of two cycles. The sample of the research was one group out of four groups of the first semester students’ of English Department of Nommensen KHBP university which was selected by using random sampling technique. Listening test, observation sheets and diary notes were employed to collect the data. Quantitatively, it showed that there were an improvement of listening ability from the students since the first up to the last treatments. The result showed that in the first treatment there is no students who got the point up to 75. But it increased to 37.5% in the end of the second treatment and 94.28% in the end of the last treatment. Qualitatively, the result showed that the students felt better, easier, and interesting to learn listening that leading to the acquirement of more successful listening comprehension skill. Therefore, shadowing technique could be used to improve students’ ability in listening comprehension. Keywords: Listening comprehension, shadowing technique